Carbon Ink Characterization from Banana and Cassava Peels by Carbonization Method - Siti Fatimah; Nimas Mustika; Suci Pratiwi (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
Banana and cassava plants are the most growing plants in the world. The use of both plant's peel is usually for animal feed. This research is intended to utilize banana and cassava peel as a raw material of whiteboard ink markers by varying concentration of the carbons to see its effect on the characteristics of the ink.  The carbon concentration variations are 25 g, 30 g, 35 g, 40 g, and 45 g, which is dissolved in 100 ml of the solution. The steps of this research include the carbonization of banana or cassava peel, and then its carbon powder is sifted by 200 mesh. The powder will be dissolved in 50 ml of Arabic gum 10%, 15 ml of PEG-7, and 35 ml of alcohol 70%, then the solution stirred until homogeneous. The result showed that the addition of the Banana or cassava peels carbon concentration effect on the value of density, viscosity, pH, and pigment ink. The characteristic whiteboard ink markers from the banana peel that accordance with the commercial ink. It is consists of 30% Banana peel carbon concentration with a density value of 1.0077 g/cm3, viscosity value of 6.2049 cP, pH value of 10.55, and the ink pigment are close enough with the commercial refill ink. While the characteristic from cassava consists of 35% cassava peel carbon concentration with a density value of 1.0893 g/cm3, viscosity value of 15,2427 cP, pH value of 8,75, and the ink pigment are close enough with the commercial ink